Option theory - James, Peter, 1943- (Hoboken, NJ : J. Wiley, 2003)
This book is aimed at busy financial engineers at all levels, providing formulas and techniques that can be readily applied to real life problems.
Includes bibliographical references ([361]-365) and index.
osa 23/07/14
Loans
Keywords: Options (Finance)